Extracts of cryopreserved organ fragments of pigs and piglets as a component of restorative medicine - Halchenko, S.Ye.; Sandomirsky, B.P. (Reports of the National Academy of Sciences of Ukraine, 2017)
The peptide composition of the extracts of cryopreserved fragments of organs of pigs and piglets and their biological activity under experimental pathological states are studied. It is shown that the release of peptides to the solution was higher from cryopreserved fragments of organs of pigs and piglets, and the molecular-mass distribution of peptides in the extracts depends on organ and age of animals. When incubating both control and cryopreserved organ fragments in the presence of proteinase inhibitors, the concentration of peptides in supernatant was statistically significantly lower than after the incubation without it. These extracts are shown to stimulate the process of reparative regeneration under experimental pathological states of the corresponding organs (hepatitis, hepatic cirrhosis, cold wound, myocardial necrosis, spontaneous myocardial ischemia). It is established that the injections of piglet heart extracts to rats stimulate the cell proliferative activity in myocardium.